(untitled) (Third Sector Social Economic Review, 2018)
The Islamic banking model, which was developed as an alternative model to traditional banking, has become increasingly important and grown since the beginning of the 1960s. In Turkey, the Islamic banking practices was first started under the name of private financial institutions then continued as participation banking. This model started to be implemented in Turkey in the 1980s. It still exists today. In parallel to increasing importance of the participation banking in Turkey, the number of graduate studies prepared on this subject has also increased. In this study, a first in the field, the content of the graduate dissertations prepared in the participation banking sector in Turkey was analyzed.